Influence of environmental factors on the growth of Colletotrichum godetiae, causal agents of olive anthracnose in Spain - Expósito‐Díaz, Anabel; Medina, Angel; Moral, Juan (Wiley, 2026)
Olive anthracnose, the most critical disease affecting fruit and oil quality, is caused by Colletotrichum species, with C. godetiae dominant in Italian and Spanish orchards. Climate change could exacerbate its impact, particularly through rising temperatures and altered CO2 levels. This study evaluated the growth of two C. godetiae strains (Col-558 and Col-493) on Potato Dextrose Agar (PDA) and ‘Picudo’ fruit-agar medium in different assays. Firstly, the strains were incubated at 10°C, 20°C, 25°C and 35°C and CO2 concentrations of 400 and 1000 ppm. Secondly, both strains were grown at the same temperatures but at different water activity (aw) levels (0.90, 0.94 and 0.98). Temperature was the main factor affecting fungal growth, explaining 64.2% of the variance in lag time and growth rate; CO2 had no significant effect. Conversely, aw and temperature significantly influenced mycelial growth, contributing 38.0% and 34.2% of the variance, respectively. An aw of 0.90 consistently resulted in a lag time exceeding 14 days across all temperatures. Furthermore, no growth was observed at 35°C under any aw or media conditions. These findings enhance our understanding of the environmental constraints on C. godetiae growth, highlighting the need for further research to develop mitigation strategies for olive anthracnose.
Keywords: climate change; Colletotrichum spp.; fungal growth conditions; olive anthracnose; 3108 Plant Biology; 31 Biological Sciences; Microbiology; 3103 Ecology; 3104 Evolutionary biology; 3107 Microbiology; Colletotrichum; Olea; Plant Diseases; Spain; Temperature; Culture Media; Carbon Dioxide